2015
DOI: 10.1016/j.ajhg.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Penetrance of Hemochromatosis in HFE Genotypes Resulting in p.Cys282Tyr and p.[Cys282Tyr];[His63Asp] in the eMERGE Network

Abstract: Hereditary hemochromatosis (HH) is a common autosomal-recessive disorder associated with pathogenic HFE variants, most commonly those resulting in p.Cys282Tyr and p.His63Asp. Recommendations on returning incidental findings of HFE variants in individuals undergoing genome-scale sequencing should be informed by penetrance estimates of HH in unselected samples. We used the eMERGE Network, a multicenter cohort with genotype data linked to electronic medical records, to estimate the diagnostic rate and clinical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 28 publications
10
36
0
2
Order By: Relevance
“…Among patients with hemochromatosis, or iron-overload-related disease, the prevalence of C282Y homozygotes in the human hemochromatosis ( HFE ) allele was investigated in three studies (Allen et al, 2008; McLaren et al, 2008; Scotet et al, 2005). HFE regulates iron uptake by controlling the relationship between transferrin and the transferrin receptor (Gallego et al, 2015). All three studies observed significant associations between C282Y and fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Among patients with hemochromatosis, or iron-overload-related disease, the prevalence of C282Y homozygotes in the human hemochromatosis ( HFE ) allele was investigated in three studies (Allen et al, 2008; McLaren et al, 2008; Scotet et al, 2005). HFE regulates iron uptake by controlling the relationship between transferrin and the transferrin receptor (Gallego et al, 2015). All three studies observed significant associations between C282Y and fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…1:16) in the Caucasian population, but accounts for a phenotype only in a minority of cases . A more common HH variant (MAF = 17% in the 1000 Genomes European population) is c.187C > G, p.His63Asp, which causes a milder degree of iron overabsorption and is most relevant to disease when paired with the allele for p.Cys282Tyr in compound heterozygotes . In the context of increased intestinal iron absorption, HFE mutations could protect against the development of iron deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genetic results could influence management of iron supplementation or influence iron level monitoring. 10 Indeed, multiple genes seem to have an effect on iron levels, and these should be considered as candidates that influence disease penetrance. 11…”
Section: Heritable Disease and Penetrancementioning
confidence: 99%